STRATEGI KOMUNIKASI INTERPERSONAL GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SDN AREN JAYA VII KOTA BEKASI - Adinda Tiara; Siti Qona'ah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study was motivated by the decline in students' academic performance from grades 1–6 at SDN Aren Jaya VII Bekasi City during the first semester, which was associated with low learning motivation. In the second semester, students' performance improved after teachers implemented more effective communication strategies. This study aims to describe teachers' interpersonal communication strategies in improving students' learning motivation. A descriptive qualitative approach was employed using Joseph A. DeVito's interpersonal communication theory, which includes openness, empathy, supportiveness, positiveness, and equality. Data were collected through interviews, observations, documentation, and literature review involving six homeroom teachers as key informants and three students as supporting informants. Data were analyzed using the Miles and Huberman model, consisting of data collection, reduction, presentation, and conclusion drawing. The findings indicate that teachers applied interpersonal communication in an open, empathetic, supportive, positive, and fair manner, which enhanced students' participation, self-confidence, and learning motivation. Therefore, teachers' interpersonal communication plays an important role in improving students' learning motivation.